2021
DOI: 10.1590/1809-4392202003582
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the mangrove oyster, Crassostrea rhizophorae (Bivalvia: Ostreidae) cultured in a macrotidal high-salinity zone on the Amazon mangrove coast of Brazil

Abstract: This study aimed to establish the reproductive cycle of the mangrove oyster, Crassostrea rhizophorae cultured in the macrotidal estuary of the Paciência River, Maranhão state, on the northeastern coast of Brazil, and its relationship with environmental factors. Oysters were collected monthly throughout 2013 for histological analysis of sex ratio, gonadal development and condition index. The sex ratio was 1:1.39 (M:F) and only 5 specimens presented hermaphroditism. The breeding process was continuous throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
(32 reference statements)
2
1
1
Order By: Relevance
“…Throughout the sampling period, M. bilineata was observed to spawn in most months in Mengkabong Bay. This finding is consistent with previous studies suggesting that spawning may occur year-round in tropical regions (Castilho-Westphal et al, 2015;Antonio et al, 2021). The relatively constant temperature and salinity conditions in Mengkabong Bay (from 26.58 to 29.14 psu and from 29.56 to 30.14 °C, respectively) appear to be the primary drivers of continuous M. bilineata reproduction (Tan and Ransangan, 2014; Cárdenas and Aranda, 2000).…”
Section: Histological Studies Of Gonadssupporting
confidence: 92%
See 2 more Smart Citations
“…Throughout the sampling period, M. bilineata was observed to spawn in most months in Mengkabong Bay. This finding is consistent with previous studies suggesting that spawning may occur year-round in tropical regions (Castilho-Westphal et al, 2015;Antonio et al, 2021). The relatively constant temperature and salinity conditions in Mengkabong Bay (from 26.58 to 29.14 psu and from 29.56 to 30.14 °C, respectively) appear to be the primary drivers of continuous M. bilineata reproduction (Tan and Ransangan, 2014; Cárdenas and Aranda, 2000).…”
Section: Histological Studies Of Gonadssupporting
confidence: 92%
“…The Magallana bilineata population in Mengkabong Bay was found to be female-biased at a ratio of 1:2.36. These findings are consistent with those of several other Crassostrea species, including Crassostrea (M.) saidii, C. brasilliana, C. cortezieensis, C. gigas, and C. rhizophorae (Castilho-Westphal et al, 2015;Ezgeta-Balić et al, 2020;Antonio et al, 2021;Barman et al, 2022). Conversely, several Crassostrea species have been reported to be malebiased (Rodríguez-Jaramillo et al, 2008) or have similar or almost equal sex ratios (Castaños et al, 2009;Vaschenko et al, 2013;Dridi et al, 2014).…”
Section: Histological Studies Of Gonadssupporting
confidence: 89%
See 1 more Smart Citation
“…Spawning in oysters in the tropics may occur through most of the year, with peaks usually before and after the rainy season (Quayle 1980). Antonio et al (2021) stated that low variation in temperature might be the main factor in continuous spawning in tropical regions. There were variations in the spawning season and spawning peaks between and within the tropical oyster species depending on habitat localities (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Yigitkurt et al (2020) reported that the most important environmental parameters triggering reproduction in bivalves are temperature and chlorophyll-a and that the amount of chlorophyll-a increases in parallel with the increase in temperature. Antonio et al (2021) reported that environmental parameters such as food availability and TPM can affect the reproductive cycle of oysters. However, in this study, no correlation was found between the number of newly attached individuals, chlorophyll-a, and TPM (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%